Evaluating Renal Benefits of Rivaroxaban Versus Vitamin K Antagonists in Atrial Fibrillation: A Systematic Review and Meta-analysis of Real-world Evidence - Phong Phan Dinh; Tri Huynh Quang Ho; Hung Manh Pham; Hai Hoang Nguyen; Minh That Ton; Giang Song Tran; Nga Quynh Vu; Hung Nhu Pham; Son Cao Luong; Sy Van Hoang (European Cardiology Review)
Background: AF is a global health concern, with systemic complications including renal dysfunction. This systematic review and meta-analysis compares the effects of rivaroxaban, a Factor Xa inhibitor, and vitamin K antagonists (VKAs) on renal outcomes in AF patients. Methods: The study protocol is registered in PROSPERO (ID: CRD42023462756). We systematically searched the PubMed, Embase and Cochrane Library databases from 1 January 2017 to 30 June 2023 for real-world studies comparing the effects of rivaroxaban and VKAs on renal outcomes in AF patients, including acute kidney injury, a ≥30% decrease in estimated glomerular filtration rate, doubling of serum creatinine and worsening renal function. Subgroup analyses targeted diabetes, pre-existing kidney disease, the elderly (age ≥65 years) and Asian populations. The risk of bias was assessed used the Robins-I tool. HRs and 95% CIs were synthesised through a random-effects model. Two sensitivity analyses were performed, using a fixed-effects model and excluding conference abstracts. Results: We identified 1,666 records. After screening, 14 studies comparing rivaroxaban and VKAs were included. Rivaroxaban exhibited superiority over VKAs in preventing: acute kidney injury (HR 0.68; 95% CI [0.61–0.77]; p<0.00001); a ≥30% decrease in estimated glomerular filtration rate (HR 0.71; 95% CI [0.60–0.84]; p<0.0001); doubling of serum creatinine (HR 0.50; 95% CI [0.36–0.70]; p<0.0001); and worsening renal function (HR 0.56; 95% CI [0.45–0.69]; p<0.00001). Subgroup and sensitivity analyses consistently confirmed rivaroxaban’s favourable effects on renal outcomes in diabetes, pre-existing kidney disease, the elderly and Asian populations. Conclusion: Our findings support the preference of rivaroxaban over VKAs for renal outcomes in AF. The findings endorse rivaroxaban as the preferred anticoagulant to mitigate renal complications, offering clinicians valuable insights for tailored strategies.